Pilot Sequence Allocation Schemes in Massive MIMO Systems Using Heuristic Approaches - Everton Alex Matos; Robson Parmezan Bonidia; Danilo Sipoli Sanches; Rogério Santos Pozza; Lucas Dias Hiera Sampaio (Applied Sciences, 2022)
This paper presents a comparison of different metaheuristic approaches applied to the pilot sequence allocation problem in Massive Multiple-Input Multiple-Output (MIMO) systems. A modified version of the Genetic Algorithm (GA) as well as different versions of the Particle Swarm Optimization (PSO) Algorithm are used to maximize the system spectral efficiency under an inter-cell interference regime. The metaheuristic parameters were optimized and computational simulations under different scenarios parameters were conducted to verify the system performance impact in terms of system spectral efficiency, minimum and maximum spectral efficiency per user and the cumulative distribution function (CDF) of the users spectral efficiencies. The main contributions of this work are: the creation of a public available dataset; heuristic parameters tuning; findings related to the impact of sub-optimal pilot sequence allocation to the users in terms of maximal and minimal achievable user spectral efficiency and the robustness of some algorithms in scenarios with different system loadings.